Contributions of safety critical success factors and safety program elements to overall project success - Buniya, M.K. (Taylor and Francis Ltd., 2022)
Implementing a safety program is an essential step toward improving safety performance. This research aims to develop an overall project success (OPS) model for building projects through investigating the direct and indirect impact of safety critical success factors (CSFs) on OPS mediated by safety program elements. First, interviews were carried out with experts in the Iraqi construction industry, and then a questionnaire survey was utilized to obtain feedback from construction professionals. The results revealed that 20 elements are needed to confirm and improve effectiveness. These elements were categorized into four constructs: management commitment and employee involvement, worksite analysis, hazard and prevention control, and health and safety training. The analysis confirms that the relationship between safety CSFs and OPS are mediated by safety program elements. These findings offer a glimmer of hope for implementing safety programs in the Iraqi construction sector, and can also be used to enhance safety performance. Â© 2022 Central Institute for Labour ProtectionâNational Research Institute (CIOP-PIB).